Estrategias de control y prevención de la diarrea epidémica porcina en la productividad de granjas de cerdos - Murillo Olvera, Eliana Mylena (2025)
Porcine epidemic diarrhea (PED) is a highly contagious pathology that affects the swine industry, causing significant economic losses due to its rapid spread and high mortality in piglets. The objective of the study was to analyze the control and prevention strategies for porcine diarrhea, focusing on biosafety measures, health control and staff education. In the methodology, a qualitative and descriptive methodology was used based on an exhaustive bibliographic review of primary sources such as articles and magazines. The results show that hygiene in the facilities, vaccination processes and restriction in accessibility to farms are determining factors to reduce the spread of the disease, likewise the training of personnel in biosafety protocols is important for the sustainability of the sector, the implementation of the strategy significantly reduces the incidence of the pathology and optimizes production on the farms. In conclusion, porcine epidemic diarrhea is transmitted through mechanical vectors such as the use of infected tools and movement of animals, which emphasizes the need to apply strict sanitary measures, the education of personnel and the adoption of effective preventive practices play an important role in the eradication and control of the pathology, ensuring safe and stable porcine production. It is recommended to implement different strict disinfection protocols for equipment and facilities, in addition to restricting the accessibility of people and vehicles within the farm in this way quarantine is established for the new animals.